ACCOUNTING FOR INVENTORIES BASED ON PSAP NUMBER 05 AT THE DPRD SECRETARIAT OFFICE, NORTH NIAS REGENCY - Dedi Irawan Zebua (SEAN Institute, 2023)
The objective to be achieved in this study is to determine whether inventory accounting at the Office of the DPRD Secretariat in North Nias Regency is in accordance with PSAP Number 05. Inventories are current assets in the form of goods or equipment to support operational activities in government agencies. A good inventory recording system and in accordance with applicable accounting principles can improve the performance of services carried out by government agencies. This study aims to determine the suitability of Inventory Accounting based on Government Accounting Standards Statement (PSAP) Number 05, which is applied at the North Nias DPRD secretariat office. The data collection techniques used are interviews and observations. The results showed that inventory accounting in the North Nias DPRD secretariat office was mostly in accordance with the Statement of Government Accounting Standards (PSAP) No.05.